Idaho! - Ross, Dana Fuller (Toronto New York Bantam Books, 1984)
Only the most daring cross the River of No Return to enter this wild, lawless region. Mountains laden with riches lured prospectors burning with gold fever. Easy money brought ruthless young men with guns for hire. And hidden amid the vast forests of white pine were the war ponies of Shoshoni and Nez Perce--bloodthirsty Indian warriors who gathered to drive the white man from the red man's ancestral home.
89580
Keywords: Idaho -- History -- Fiction; Historical fiction